2006
DOI: 10.1063/1.2360236
|View full text |Cite
|
Sign up to set email alerts
|

Photonic band tuning in two-dimensional photonic crystal slab waveguides by atomic layer deposition

Abstract: The photonic bands of two-dimensional (2D) triangular lattice photonic crystal Si slab waveguides were statically tuned using low temperature atomic layer deposition (ALD) of TiO2. Angular dependent reflectance measurements of bare and coated devices were well fitted by three-dimensional finite-difference time-domain calculations. The technique not only allows the physics of photonic band effects in 2D photonic crystals to be systematically studied but also demonstrates large static tuning and precise fine-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…A scanning electron microscope (SEM) image of a Ni inverse opal is shown in Figure 6-4. The Al 2 O 3 dielectric was deposited using atomic layer deposition (100 cycles), which was previously shown to be conformal within 2D [139] and 3D porous structures, [140][141][142] assuming enough time is allotted to allow the precursors to diffuse into the structures. However, we were unable to directly observe the conformal dielectric layer in the SEM due to the thickness of the Al 2 O 3 (ca.…”
Section: Resultsmentioning
confidence: 99%
“…A scanning electron microscope (SEM) image of a Ni inverse opal is shown in Figure 6-4. The Al 2 O 3 dielectric was deposited using atomic layer deposition (100 cycles), which was previously shown to be conformal within 2D [139] and 3D porous structures, [140][141][142] assuming enough time is allotted to allow the precursors to diffuse into the structures. However, we were unable to directly observe the conformal dielectric layer in the SEM due to the thickness of the Al 2 O 3 (ca.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications of such structures by ALD can improve their potential use as optical elements e.g., in holography. ALD-TiO 2 was employed to tune the static photonic band of a 2D Si triangular lattice PC slab waveguide by nanoscale control of the dielectric contrast, propagation, and dispersion (Graugnard et al, 2006). This research group also reported the fabrication of 3D nano-structures through synthetic silica opals and holographically patterned polymeric templates to control PC band gap properties (Graugnard et al, 2006).…”
Section: Conformal Growth For 2d and 3d Structuresmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images in Figure 3A show the conformal growth of ALD-TiO 2 films of various thicknesses of (0-120 nm) on Si triangular lattice of photonic crystals (PCs) (Graugnard et al, 2006). Transmission Electron Microscopy (TEM) images of four-bilayer nanolaminates of W/Al 2 O 3 grown by ALD at temperature of 177°C are shown in Figure 3B (Sechrist et al, 2005 More often, the ALD film growth is a fraction of one monolayer and has higher film density to those of films deposited by other techniques without pinhole defects (Carcia et al, 2009;Saleem et al, 2012bSaleem et al, , 2013c.…”
Section: Self-controlled Film Thickness and Materials Compositionmentioning
confidence: 99%
“…A PCS is a one-or two-dimensional periodically patterned dielectric slab [24,25]. In-plane guided modes connement of light can be done by the higher refractive index (RI) dielectric material or can be guided resonance modes in the slab,…”
Section: Introductionmentioning
confidence: 99%